Role of fluid-structure interaction in mixed convection from a circular cylinder in a square enclosure with double flexible oscillating fins. (October 2019) - Saleh, H.; Siri, Z.; Hashim, I.
Highlights: FEM and Arbitrary Lagrangian-Eulerian (ALE) procedure are used in the numerical analysis. Two solid elastic thin fins are attached on the top cold wall. Elasticity of the flexible fin can highly improve the heat transfer. The results revealed an essential effect of the fin direction on the flow and heat transfer. Abstract: The problem of unsteady mixed convection in a square enclosure containing a heated circular cylinder is studied in this paper. Two solid elastic thin fins are attached on the top cold wall. The governing equations for fluid flow and energy in the fluid and structures domains are written in Arbitrary Lagrangian-Eulerian (ALE) formulation. Finite element method was used to obtain the approximate solutions of the governing equation. The governing parameters considered are the oscillating fin direction, fin amplitude and length with various elasticity values and cylinder sizes. The results show that the instantaneous heat transfer characteristics of the contrary oscillation differs greatly from the identical oscillation. The influence of the elasticity value on the heat transfer rate is significant at a sufficiently small amplitude oscillation.